Association between Neonatal Phototherapy and Cancer during Childhood - Maliheh Kadivar; Razieh Sangsari; Maryam Saeedi; Shadi Ghasemi Tehrani (Mashhad University of Medical Sciences, 2020)
Background: Phototherapy is the most effective and commonly used treatment for neonatal jaundice, which reduces the need to exchange transfusion. Today, phototherapy is widely used even in unnecessary cases; however, clinicians who use phototherapy should be aware of the possible adverse effects of this treatment to avoid unnecessary use of it. Therefore, this study aimed to evaluate the relationship between neonatal phototherapy and childhood cancer. Methods: This case-control study assessed 500 children up to 14 years of age with every kind of cancer that referred to Children's Medical Center, Tehran, Iran, during 2015-18. Moreover, 500 children without cancer referring to a General Clinic of Children's Medical Center, Tehran, Iran were included in this study as the control group. History of phototherapy and its duration evaluated in these two groups. Furthermore, demographic characteristics, including maternal age during pregnancy, birth weight, gender, smoking by father, type of cancer, age at cancer detection, and history of cancer in relatives were recorded in this study. Results: The results of a single-variable logistic regression showed that neonatal phototherapy without any other variables was not significantly correlated with childhood cancer. However, phototherapy will increase the risk of cancer by 55% when it is accompanied by the male gender, maternal age >35 years during pregnancy, and smoking by father. Conclusion: The potential risk of developing cancer with neonatal phototherapy should be considered versus its benefits in reducing the bilirubin.